Implementasi Kebijakan Pelayanan Administrasi Kependudukan Secara Daring Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Deli Serdang - Yuli Ajizah Hasibuan; Rudi Salam Sinaga; Adam Adam (Universitas Medan Area, 2022)
Therefore, the authors are interested in conducting research that aims to find out and analyze the implementation and policy constraints of the Minister of Home Affairs Regulation no. 7 of 2019 concerning Online Population Administration Services at the Deli Serdang Regency Population and Civil Registration Service. The research approach used in this study is a qualitative approach, namely problem solving procedures investigated by describing the current state of the subject/object of research based on visible facts. The results of the study found that the application of online population administration services at the Deli Serdang Regency Population and Civil Registration Service had been carried out in accordance with the Minister of Home Affairs Regulation Number 7 of 2019 so that population administration documents could be served. This can be seen from communication, socialization of resources, disposition and bureaucratic structure. The obstacles faced by agencies in implementing online population administration services according to the Minister of Home Affairs Regulation Number 7 of 2019 are: information systems that are densely used/accessible so that they are constrained in speed of service, lack of funds to be able to improve existing facilities and infrastructure, and lack of employee desire. to improve the quality of public services.